Financial management in academic libraries : data-driven planning and budgeting - Dugan, Robert E., 1952-; Hernon, Peter (Association of College and Research Libraries, a division of the American Library Association, 2018)
Financial Management in Academic Libraries explores the connection between financial management and accountability, effectiveness, efficiency, and sustainability, and demonstrates how to capture them in a realistic, data-supported budget. Among the different units of an academic institution, the library has an advantage in that its managers can link these concepts to the library's infrastructure, its staffing, collections, services, and technology. Focusing on these components can enable everyone in the library to work to achieve organizational sustainability over time and advocate for their place in the institution.